Merjenje lomnega količnika s fiberoptičnim odbojnostnim senzorjem - Suhadolnik, Alojz (Informacije MIDEM, 1992)
In this contribution, the optical fiber reflection sensor for the determination of the refractive index of liquids is described. The measuring system has an accuracz of 0.001. The experimental results of refractive index measurements of aqueous solutions of NaCl are presented.
Keywords: characteristic measurement; eksperimentalne raziskave; eksperimentalni rezultati; experimental research; experimental results; fibre optic sensors; lomni količnik; merjenje karakteristik; merjenje koncentracije raztopin; odbojnostni senzorji; optic fibres; optična vlakna; reflection sensors; reflective index; solution concentration measurements; vlakenskooptični senzorji